Model Komunikasi Pemasaran untuk Pemberdayaan Perempuan Pada Sektor Informal di Yogyakarta - Sauptika Kancana; Puji Lestari; Fera Nurficahyanti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2016)
This research aims to find out model of communication marketing as means to increasing the power of women’s UKM in informal sector of Yogyakarta. Research methodology in qualitative descriptive is used with collect data, focus group discussion (FGD). These research methodogy are service, food, and farm. Result of this research found model of communication marketing which is used media social methodology in informal sector to increasing the power of women’s UKM of Yogyakarta. This research extend give recommendation for women’s UKM of Yogyakarta to optimize their effort through social media such as facebook, twitter, instagram, and website.